2018
DOI: 10.1016/j.amepre.2018.04.030
|View full text |Cite
|
Sign up to set email alerts
|

Isoniazid-Rifapentine for Latent Tuberculosis Infection: A Systematic Review and Meta-analysis

Abstract: The 3-month isoniazid-rifapentine regimen is as safe and effective as other recommended latent tuberculosis infection regimens and achieves significantly higher treatment completion rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 32 publications
0
41
1
4
Order By: Relevance
“…Shorter rifamycin‐based regimens (e.g. weekly rifapentine plus isoniazid for 12 weeks and daily rifampicin for 4 months) are proving safe and effective alternatives to 9 months of isoniazid, especially in terms of lower risk of hepatotoxicity. However, the risks of other adverse effects (e.g.…”
Section: Tuberculosismentioning
confidence: 99%
See 1 more Smart Citation
“…Shorter rifamycin‐based regimens (e.g. weekly rifapentine plus isoniazid for 12 weeks and daily rifampicin for 4 months) are proving safe and effective alternatives to 9 months of isoniazid, especially in terms of lower risk of hepatotoxicity. However, the risks of other adverse effects (e.g.…”
Section: Tuberculosismentioning
confidence: 99%
“…However, the risks of other adverse effects (e.g. systemic or hypersensitivity reactions to rifamycins) remain considerable relative to the number of TB cases averted. A targeted approach is therefore necessary to optimize the benefit versus risk ratio at the expense of reduced population coverage .…”
Section: Tuberculosismentioning
confidence: 99%
“…For rifampin and rifapentine, plasma exposures higher than those achieved with current doses result in improved antituberculosis activity and appear to be relatively safe. Recent and ongoing clinical studies are likely to broadly redefine the optimal dosing strategies for these rifamycins and other drugs in treatment and preventive therapy regimens [19][20][21][22][23][24]. Evidence is needed to inform appropriate doses for tuberculosis at sites where penetration of the drugs into the diseased compartments is limited such as tuberculous pericarditis and tuberculous meningitis [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of INH, despite occurring quite commonly, the considerable majority are low grade, transient and do not influence treatment adherence and completion . A recent meta‐analysis demonstrated that the three‐month isoniazid‐rifapentine regimen was associated with similar risk of adverse events and treatment discontinuation than other latent tuberculosis infection regimens . Regarding drug‐drug interactions (DDI) between TPT regimes and the existing ART, there are still some knowledge gaps to cover, such as co‐administration of TAF with any rifamycin, or use of 1HP with DTG.…”
Section: Discussionmentioning
confidence: 99%